Examining the Impact of Career Development and Work-Life Balance on Career Decisions of Interning Students - Fauziah, Sarah; Maulana, Muhamad Akbar; Wibowo, Sandi Nasrudin (UPT Jurnal & Publikasi Ilmiah SPs Universitas Ibn Khaldun Bogor, 2025)
Internship programs play a crucial role in bridging academic knowledge with professional practice, yet their impact on career decisions remains underexplored. This study investigates how career development and work-life balance influence the career decisions of university interns, with a focus on the moderating role of work-life balance. A quantitative approach was employed, utilizing Partial Least Squares - Structural Equation Modeling (PLS-SEM) to analyze data from 174 internship students at PT United Tractors Tbk MSIB Batch 6 in Indonesia. Data were collected through Likert-scale questionnaires measuring career development, work-life balance, and career interest. Statistical analysis, including validity, reliability, and moderation tests, was conducted using SmartPLS 3. Career development significantly and positively affected interns’ career decisions (β = 0.344, p < 0.001), as did work-life balance (β = 0.261, p < 0.001). Furthermore, work-life balance strengthened the relationship between career development and career decisions, acting as a significant moderator (β = 0.748, p < 0.001). The model explained 58.2% of the variance in career decisions. Internship programs that integrate structured career development initiatives and prioritize work-life balance are essential for fostering career readiness. Organizations should offer mentorship, flexible schedules, and skill-building opportunities, while universities should equip students with strategies to manage professional and personal responsibilities. These findings underscore the need for holistic internship designs that address both technical and well-being aspects.